Hubungan tingkat kecemasan dengan kejadian hipertensi - Nugraha, Ilham Cahya; Asmarawanti, Asmarawanti; Utami, Rima Novianti (Published by: Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2026)
Background: Hypertension is a major health problem in the elderly, and anxiety is a contributing factor, which can trigger sympathetic nervous system activation and increase blood pressure. Purpose: To determine the relationship between anxiety levels and the incidence of hypertension. Method: This quantitative study used a correlational analytical design and a cross-sectional approach. The population was all hypertensive patients (157), with a sample size of 61 individuals using stratified random sampling. Data analysis used the Chi-Square test. Results: Most respondents had stage 1 hypertension (54.1%), and nearly half had severe anxiety (44.3%). The Chi-Square test showed a 0.001<0.05 indicating a significant relationship between anxiety levels and the incidence of hypertension. Conclusion: There is a significant relationship between anxiety levels and the incidence of hypertension, therefore, psychological aspects need to be part of comprehensive interventions in managing hypertension in the community. Keywords: Anxiety; Elderly; Hypertension. Pendahuluan: Hipertensi merupakan masalah kesehatan utama pada lansia dan salah satu faktor yang berkontribusi adalah kecemasan, yang dapat memicu aktivasi saraf simpatis dan peningkatan tekanan darah. Tujuan: Mengetahui hubungan tingkat kecemasan dengan kejadian hipertensi. Metode: Penelitian kuantitatif dengan desain analitik korelasional dan pendekatan cross sectional. Populasi adalah seluruh pasien hipertensi (157 orang), dengan sampel 61 orang menggunakan teknik stratified random sampling. Analisis data menggunakan uji Chi-Square. Hasil: Sebagian besar responden berada pada kategori hipertensi derajat 1 (54.1%) dan hampir setengahnya memiliki kecemasan berat (44.3%). Uji Chi-Square menunjukkan nilai 0.001<0.05 yang berarti terdapat hubungan bermakna antara tingkat kecemasan dan kejadian hipertensi pada pasien. Simpulan: Terdapat hubungan signifikan antara tingkat kecemasan dengan kejadian hipertensi, sehingga aspek psikologis perlu menjadi bagian dari intervensi komprehensif dalam pengelolaan hipertensi di masyarakat. Kata Kunci: Hipertensi; Kecemasan; Lansia.